Pesan Dakwah dalam Antologi Puisi Buku Jalan Ini Rindu Karya W.A.A Ibrahimy - Nur Dina Kholida; Yohandi (Maddah : Jurnal Komunikasi dan Konseling Islam, 2022)
Poetry is one of the works of literary art. Poetry is created by containing certain messages ex- pressed by poets to be conveyed to readers. These messages can be in the form of human values, li- fe problems, religious and so on. The literary language that is packaged in poetry is very beautiful. However, not everyone can understand the language used. There are several languages that may be considered highly for some people to be able to understand the meaning of the writing. For this re- ason, the purpose of this research is to describe the message of da’wah in the Anthology of Poetry Books Jalan Ini Rindu by W.A.A Ibrahimy. This study uses library research methods (library rese- arch). The data source that the author uses is the primary data source, namely the Anthology of Po- etry Books Jalan Ini Rindu by W.A.A Ibrahimy. While the supporting data the author obtained from books, and the internet. Collecting data using documentary literature, namely by reading, studying, understanding, and reviewing the sources of library data from this anthology of poetry by W.A.A Ibra- himy. The data analysis technique uses content analysis which is carried out through the process of identifying and examining the messages contained in a text. The results of the study concluded that in the poetry of this book of longing there are messages of preaching Akidah, Shari’a, and Akhlak. In the poem “Cakrawala Basamalah” it contains the message of the Da’wah of Akidah, which is about faith in Allah SWT. in the poem “In Sujudku” contains the message of Shari’a da’wah, namely about praying. Furthermore, the poem “Until your prayer” contains a message of moral preaching, which is about filial piety to both parents.